Additional muscle in the popliteal fossa – a potential source of entrapment of tibial nerve. - Surekha, DS; Satheesha, NB; Naveen, K; Jyothsna, P (Department of Surgery, UKM Medical Centre, 2013)
Popliteal fossa is a diamond shaped intermuscular space posterior to the knee joint. It contains the popliteal vessels and terminal branches of sciatic nerve, embedded in the fat. Presence of any additional muscle slips in this region can entrap/compress the nerves and vessels, leading to neurovascular symptoms. We here report the presence of an additional muscle in the popliteal fossa. The muscle had a tendinous origin from the fascia covering the popliteal vessels. The fleshy belly of the muscle was lying superficial to the popliteal vessels and the tibial nerve. The tibial nerve passed from medial to lateral side undercover of the additional muscle. The muscle had a distal tendon that merged with the medial head of the gastrocnemius muscle. It was innervated by a branch from the tibial nerve. The muscle was small and weak to cause any significant movement at the knee joint but was large enough to cause any neurovascular compression/entrapment symptoms.